보육교사의 수요 전망 - 이미화(Mee Hwa Lee); 신나리(Na Ry Shin); 김현철(Hyun Chul Kim); 김문정(Moon Jeong Kim) (Korean Journal of child studies, 2007)
The purpose of this study was to estimate the future demand for certified teachers at childcare centers. This is an essential step to secure the supply of childcare teachers in the future. To achieve this purpose, the demand for childcare teachers from 2006 to 2020 were estimated using time series techniques with data on the number of childcare teachers from 2002 to 2005. According to time series estimates, the demand for childcare teachers is expected to increase steadily from 1,224 to 1,956 annually. This illustrates the need for mid-term and long-term planing in order to guarantee an adequate supply of childcare teachers.